Firm Value and Real Earnings Management: Moderating Role of Board Independence and CEO Duality - Adhitya Agri Putra; Meliza Putriyanti Zifi (Jurnal Akuntansi Keuangan dan Bisnis, 2022)
This research aims to examine the moderating role of board independence and CEO duality on the effect of real earnings management (hereafter REM) on firm value. This research uses 867 manufacturing firm-year listed on the Indonesian Stock Exchange 2012-2019 as a research sample. Board independence includes a proportion of independent commissioners in the board, the interlock of independent commissioners. CEO duality refers to the affiliation between the CEO and the board of commissioners. REM is measured by over sales, overproduction, and discretionary expenses cutting activities. Firm value is measured by Tobin's Q. REM has a positive effect on firm value when the proportion of independent commissioner, interlock of the independent commissioner, committee overlap of the independent commissioner are higher. On the other hand, REM has a negative effect on firm value when there is a CEO duality.